The Effect of a Combination of Prolanis Exercises and Foot Exercises on Changes in Blood Glucose Levels in Type II Diabetes Mellitus Patients - Kadek Pendi Susila Yasa; Arsyawina Arsyawina; Indah Nur Imamah (International Journal of Global Sustainable Research, 2023)
Diabetes mellitus is still a global health problem as the number of suffering is still high all over the world. The recommended foot exercise for DM patients is aerobic foot exercise. To find out the effect of prolanic exercise and foot exercise on changes in blood glucose levels over time in patients with type II diabetes. The research design used in this study is a quasy experiment in the form of a two-group pretest and posttest design. The conclusions of this study have been obtained There is an influence of prolanic exercise and foot exercise on changes in blood glucose levels in patients with type II diabetes in Posyandu Manubar district of Reservoir.